Simultaneous evaluation of restless leg syndrome, neuropathic pain, disease activity, and quality of life in patients with Takayasu arteritis: a cross-sectional study - Emel Oğuz Kökoğlu; Melih Kızıltepe; Hüseyin Kaplan; Senem Şaş; Tuğba Kahraman Denizhan; Abdurrahman Soner Şenel (Scientific Reports)
Abstract We aimed to investigate the frequency of restless legs syndrome (RLS) and neuropathic pain (NeP) in patients with Takayasu arteritis (TAK), and their relationship with disease activity, and quality of life (QoL). In this prospective case-control study, we evaluated 30 patients with TAK and 28 healthy subjects. Demographic, clinical, and current treatment-related data were also recorded. RLS diagnosis was confirmed in both groups according to the International Restless Legs Study Group criteria. The Douleur neuropathic-4 questionnaire (DN4) confirmed the frequency of neuropathic pain, and the quality of life was confirmed by the Short Form 36 (SF-36) health survey questionnaire. Univariate logistic regression analyses were performed to estimate the odds ratio (OR) for factors associated with NeP in patients with TAK. There was no statistically significant difference in the diagnosis of RLS between the TAK group and the control group (p = 0.195). The prevalence of NeP was significantly higher in TAK patients than in healthy controls (p = 0.011). The SF-36 subscale scores for physical functioning (p = 0.01) and general health (p = 0.002) were significantly lower in the TAK group than in the control group. Vasculitis Damage Index (VDI) scores were considerably higher in patients with NeP (p = 0.004). In univariate analyses, VDI decreased unbound iron-binding capacity, and SF36 mental component summary were predictors associated with NeP. This study revealed that the frequency of NeP was higher in patients with TAK than in the healthy population, and the patients with TAK were negatively affected in terms of NeP and QoL rather than RLS.